2020
DOI: 10.4103/jcd.jcd_179_19
|View full text |Cite
|
Sign up to set email alerts
|

Success of pulpotomy in mature permanent teeth with irreversible pulpitis: A systematic review

Abstract: The objective of the present systematic review is to evaluate the success of pulpotomy in mature permanent teeth presented with irreversible pulpitis. The following databases were searched: PubMed, Oral and Dentistry Database, Cochrane, and CINAHL plus. We included studies published in the English language only. However, narrative reviews and case reports/series were excluded. The first electronic and hand search yielded a total of 2851 articles. After going through extensive screening and eligibility process,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 6 publications
0
17
0
2
Order By: Relevance
“…This suggests that the complete removal of infected tissue may be an important factor affecting pulpotomy of mature permanent teeth. A meta-analysis published by the Air Force Medical University in 2019 [ 82 ], the review published by Taha et al in 2020 [ 71 ]and a number of clinical studies [ 83 86 ]also confirmed from different aspects that pulpotomy is a recommended treatment for deep caries exposed pulp of mature permanent teeth or even irreversible pulpitis, which can be used as an alternative to RCT [ 87 90 ]. In addition, some studies have combined total pulpotomy and nonsurgical endodontic (NSET) for mature mandibular permanent molars diagnosed as irreversible pulpitis and apical periodontitis and achieved good results.…”
Section: Vpt Of Mature Permanent Teethmentioning
confidence: 99%
“…This suggests that the complete removal of infected tissue may be an important factor affecting pulpotomy of mature permanent teeth. A meta-analysis published by the Air Force Medical University in 2019 [ 82 ], the review published by Taha et al in 2020 [ 71 ]and a number of clinical studies [ 83 86 ]also confirmed from different aspects that pulpotomy is a recommended treatment for deep caries exposed pulp of mature permanent teeth or even irreversible pulpitis, which can be used as an alternative to RCT [ 87 90 ]. In addition, some studies have combined total pulpotomy and nonsurgical endodontic (NSET) for mature mandibular permanent molars diagnosed as irreversible pulpitis and apical periodontitis and achieved good results.…”
Section: Vpt Of Mature Permanent Teethmentioning
confidence: 99%
“…Pulpitis is a disease of dental pulp tissue infection caused by periodontal inflammation [ 1 , 2 ]. Acute retrograde pulpitis is caused by periodontal inflammation, featuring acute onset and long duration.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, based on the “AAE Guide to Clinical Endodontics (2013),” mature permanent teeth with IP should be treated with RCT, whereas VPTs were contraindicated. However, in addition to the promising outcomes of our trial, several clinical studies/trials have reported successful results for the VPT management of mature permanent teeth with signs/symptoms of IP even with AP [ 5 , 13 , 15 17 , 21 , 24 26 , 35 , 39 , 40 , 43 45 ]. There is firm evidence that severely inflamed pulpal connective tissue has great regenerative ability [ 46 ].…”
Section: Discussionmentioning
confidence: 71%
“…A randomized clinical trial, comparing the outcomes of full pulpotomy with RCT in teeth with IP, revealed that the success rate of full pulpotomy was 86% after 2 years [ 12 ]. Moreover, a recent systematic review reported 78% success for pulpotomy in teeth with IP [ 15 ]. Another trial compared 4 VPTs (indirect pulp capping, direct pulp capping, miniature pulpotomy, and full pulpotomy) using calcium-enriched mixture (CEM) cement in the management of mature molars, including teeth with IP (less than 30% in each VPT group) and apical periodontitis (AP) (~ 10%), showing high success rates for all tested groups (> 91%) after a 1-year follow-up [ 16 ].…”
Section: Introductionmentioning
confidence: 99%